2021
DOI: 10.1177/08948453211005032
|View full text |Cite
|
Sign up to set email alerts
|

Tenure Expectations and Career Aspirations Among Female Assistant Professors in STEM

Abstract: This study used social cognitive career theory to predict the career aspirations and tenure expectations of untenured female science, technology, engineering, and math (STEM) assistant professors. We hypothesized that contextual variables (perceived career barriers and institutional support for work–life balance) would directly predict career aspirations and tenure expectations. We also expected that these contextual variables would be indirectly related to career aspirations and tenure expectations through ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Given findings that women faculty in more underrepresented STEM fields less frequently reported experiencing administrative and policy support, universities should make a concerted effort to ensure they are not overlooking the needs of this group in departments where women are particularly outnumbered. Specific policies outlined in the literature that are supported by the current findings are providing flexible work scheduling, time off for childbirth or adoption, and caregiving-related breaks without penalty (Gregor et al, 2021;Hart, 2016;Moors et al, 2014). This is relevant as our study showed the demands of caregiving and professional obligations as impediments to full engagement in each area.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Given findings that women faculty in more underrepresented STEM fields less frequently reported experiencing administrative and policy support, universities should make a concerted effort to ensure they are not overlooking the needs of this group in departments where women are particularly outnumbered. Specific policies outlined in the literature that are supported by the current findings are providing flexible work scheduling, time off for childbirth or adoption, and caregiving-related breaks without penalty (Gregor et al, 2021;Hart, 2016;Moors et al, 2014). This is relevant as our study showed the demands of caregiving and professional obligations as impediments to full engagement in each area.…”
Section: Discussionsupporting
confidence: 62%
“…The importance of family-supportive leave policies has been highlighted by previous research where among STEM postdocs, the negative effect of perceived family-supportive policies on job satisfaction and sense of belonging was stronger for women than men (Moors et al, 2014). In addition, perceptions of family-supportive policies correlated positively with career aspirations and expectations of receiving tenure and negatively with impostor beliefs and perceived career barriers (Gregor et al, 2021). Given the gendered expectations of unpaid labor for women in academia at home (e.g., Toffoletti & Starr, 2016), administrative policies, such as family-supportive leave policies, could serve to reduce the unique barriers faced by women in academia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies find that women who are unsure of their science and math skills are less likely to persist in STEM career paths, as compared to women who are more confident in such skills (American Association of University Women, 2010). Successful academic performance has been linked to higher-level career aspirations among women in STEM majors (Gregor, Weigold, Martin-Wagar, & Campbell-Halfaker, 2021).…”
Section: Discussionmentioning
confidence: 99%